Russia - sporting nation: history and modernity - Parshikova, N. V.; Izaak, S. I.; Kovalenko. G. V. (Theory and Practice of Physical Culture, 2020)
Since the open confrontation of the global superpowers came to an end, the power struggle on the global arenas has been going in a variety of covert forms. In the global sports sector, the superpowers continued their competition increasingly making resort to the modern `soft power` tools on the one hand and taking efforts to increase competitiveness of the national sports to secure leadership on the global arenas on the other hand. Presently Russia is ranked number one nation by the Global Sports Nations Index - that is computed with account of the top-ranking (and national image-making) sport events hosted by every nation. It should be mentioned that Russia as a sporting nation has been on the rise for the last decade as manifested by the competitive accomplishments in the top-ranking international events and the national policies to support the large-scale popular sport projects of importance for the national image. Thus the `Russia - Sporting Nation` Forum endorsed by Presidential Decree #863 of 27.07.2009 is ranked among such popular projects. The study analyzes progress of the `Russia - Sporting Nation` Forum in the context of the national sports industry development process and emphasizes the key provisions that make it different from the alike projects in the national sport industry - including its sound regulatory framework; impressive scale of the event, its ideas and services, popularity and participation; communication service; digitalized service facilities and the international support and cooperation; and offers recommendations on how the Forum design, management and operations can be improved.